Climate Change Affects Vegetation Differently on Siliceous and Calcareous Summits of the European Alps - Nicklas, Lena; Walde, Janette; Wipf, Sonja; Lamprecht, Andrea; Mallaun, Martin; Rixen, Christian; Steinbauer, Klaus; Theurillat, Jean-Paul; Unterluggauer, Peter; Vittoz, Pascal; Moser, Dietmar; Gattringer, Andreas; et al. (Frontiers in Ecology and Evolution, 2021)
The alpine life zone is expected to undergo major changes with ongoing climate change. While an increase of plant species richness on mountain summits has generally been found, competitive displacement may result in the long term. Here, we explore how species richness and surface cover types (vascular plants, litter, bare ground, scree and rock) changed over time on different bedrocks on summits of the European Alps. We focus on how species richness and turnover (new and lost species) depended on the density of existing vegetation, namely vascular plant cover. We analyzed permanent plots (1 x 1 m) in each cardinal direction on 24 summits (24 x 4 x 4), with always four summits distributed along elevation gradients in each of six regions (three siliceous, three calcareous) across the European Alps. Mean summer temperatures increased synchronously over the past 30 years in all six regions. During the investigated 14 years, vascular plant cover decreased on siliceous bedrock, coupled with an increase in litter, and it marginally increased on higher calcareous summits. Species richness showed a unimodal relationship with vascular plant cover. Richness increased over time on siliceous bedrock but slightly decreased on calcareous bedrock due to losses in plots with high plant cover. Our analyses suggest contrasting and complex processes on siliceous versus calcareous summits in the European Alps. The unimodal richness-cover relationship and species losses at high plant cover suggest competition as a driver for vegetation change on alpine summits.